Efficient Hydrogen Evolution under Visible Light by Bimetallic Phosphide NiCoP Combined with g‐C3N4/CdS S‐Scheme Heterojunction. Issue 20 (23rd August 2021) - Ma, Wangyang; Zheng, Dewen; Xian, Yuxi; Hu, Xianhai; Zhang, Qian; Wang, Shanyu; Cheng, Congliang; Liu, Jin; Wang, Ping
Abstract: Photocatalytic hydrogen evolution is a promising method to convert solar energy. Here, the heterojunction structure of g‐C3 N4 /CdS was modified by NiCoP prepared by one‐step method for the first time, and the photocatalyst NiCoP‐g‐C3 N4 /CdS was successfully designed and prepared, which can effectively separate and transfer photogenerated electrons and efficient hydrogen evolution under visible light. Moreover, NiCoP‐g‐C3 N4 /CdS photocatalyst has abundant surface‐active sites, and its photocatalytic hydrogen evolution performance has been greatly improved. When NiCoP content was 5 % in NiCoP‐g‐C3 N4 /CdS, the catalytic activity was the highest, and the hydrogen production rate reached an astonishing 55.63 mmol h −1 g −1, which was 23.35 times that of CdS (2.38 mmol h −1 g −1 ) and 11.51 times that of g‐C3 N4 /CdS (4.84 mmol h −1 g −1 ). In addition, NiCoP‐g‐C3 N4 /CdS photocatalyst has excellent stability for hydrogen production. The materials were characterized and analyzed by XRD, SEM, TEM, XPS, UV‐Vis DRS, FTIR, UPS, N2 adsorption‐desorption process and electrochemical test etc. At the same time, the possible mechanism of NiCoP‐g‐C3 N4 /CdS photocatalytic hydrogen production reaction is proposed. This study provides a new idea for the rational design of heterojunction photocatalyst and transition metal phosphide cocatalyst. Abstract : Hydrogen evolution : A photocatalyst NiCoP‐g‐C3 N4 /CdS was prepared by using NiCoP as a cocatalyst for the modification of g‐C3 N4 /CdS heterojunction structure, which can effectively separate and transfer photogenerated electrons and efficient hydrogen evolution under visible light. Moreover, NiCoP‐g‐C3 N4 /CdS photocatalyst has abundant surface active sites, and its photocatalytic hydrogen evolution performance has been greatly improved. This study provides a new idea for the rational design of heterojunction photocatalyst and transition metal phosphide cocatalyst.